Historical dictionaries in their paratextual context (Lexicographica. Series maior, 2018)
Both dictionary and paratext research have emerged recently as widely-recognised research areas of intrinsic interest. This collection represents an attempt to place dictionaries within the paratextual context for the first time. This volume covers paratextual concerns, including dictionary production and use, questions concerning compilers, publishers, patrons and subscribers, and their cultural embedding generally. This book raises questions such as who compiled dictionaries and what cultural, linguistic and scientific notions drove this process. What influence did the professional interests, life experience, and social connexions of the lexicographer have? Who published dictionaries and why, and what do the forematter, backmatter, and supplements tell us? Lexicographers edited, adapted and improved earlier works, leaving copies with marginalia which illuminate working methods. Individual copies offer a history of ownership through marginalia, signatures, dates, places, and library stamps. Further questions concern how dictionaries were sold, who patronised them, subscribed to them, and how they came to various libraries.